Predictors of Outcome After Endovascular Thrombectomy in Acute Basilar Artery Occlusion and the 6hr Time Window to Recanalization - Ravindren, Johannes; Aguilar Pérez, Marta; Hellstern, Victoria; Bhogal, Pervinder; Bäzner, Hansjörg; Henkes, Hans (Frontiers in Neurology, 2019)
Abstract Background and Purpose: Decision algorithms for large vessel occlusions in the anterior circulation remain unconfirmed for acute basilar artery occlusion (aBAO). The aim of this study was to investigate procedural parameters, patient characteristics, functional outcome and survival in dependency of the time window to recanalization from symptom onset. Furthermore predictors of outcome were identified. Materials and Methods: Retrospectively 231 patients with aBAO treated with endovascular treatment (EVT) between November 2008 and February 2019 were identified in a prospectively maintained single center stroke database. Baseline characteristics such as age, cardiovascular risk factors, NIHSS at admission, pre interventional PC-ASPECTS, periprocedural parameters such as time to recanalization, duration of treatment, extent of reperfusion, collateral status and occlusion patterns, as well as postinterventional 24 hour NIHSS and postinterventional ICH were evaluated. Target variables were mRS 90 days and mortality over 90 days. Results: Good outcome (mRS 0-2) was attained in 29, 5% (n=68) of patients, overall mortality was 36.8% (n=85). In mulitivariate analyses Patients with time to reperfusion beyond 6 hours had a more than half fold decreased chance of good outcome (OR 0.47 95% CI (0.23-0.95) p<.05). The odds for good outcome were reduced by almost 2/3 if post interventional imaging revealed intracerebral hemorrhage (OR 0.28 95% CI (0.08-0.98)). Unfavorable outcome was noted in 100% (n=14) of patients with symptomatic ICH. Risk for death was reduced by more than 80% if collaterals were present (0.16 95% CI (0.03-0.87) and if recanalization was successful (TICI 2b-3) (OR 0.19 95% CI (0.05-0.78)). The odds for survival were 5 fold higher in patients with no postinterventional hemorrhages present (OR 5.35 95% CI (2.2-1.58)). Conclusion: This study might contribute to explaining the ambiguous findings regarding the validity of the 6 hour time window in aBAO, suggesting that collateral status impacts the odds of survival in the time window to recanalization beyond 6 hours. In our study recanalization within 6 hours from symptom onset was associated with good outcome. Successful recanalization (TICI 2b-3a) was necessary for good outcome and survival, post interventional ICH was highly associated with unfavorable outcome. This might ease the decision making for EVT.